“In un placete de La Mancha of which nombre no quiero remembrearme”: Don Quijote en spanglish y los desafíos de la traducción bilingüe - Kunz, Marco (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Spanglish, the mixing of Spanish and English in oral and written communi-cation, has an increasing importance as a literary code. Challenged by derogatory comments on the poor aesthetic possibilities of Spanglish, Mexican American scholar Ilan Stavans translated the first chapter of Cervantes’ Don Quijote into a mixed language made of English, Spanish and hybrid words. The result provoked the hilarity of many readers, but also the indignation of Castilian purists who opposed the invasion of their mother tongue by a foreign language and the desecration of the most out- standing monument of the Hispanic Culture, while American Chicanos criticized the quality of the translation, arguing that Stavans ’ Spanglish fails to reflect accurately the reality of bilingual speech in daily life. In my paper I propose some reflections about this controversy and I try to analyse Stavans’ intentions and strategies in this translation of a canonical classical text into a non-normative and highly stigmatized variety of spoken language. As it is directed to a bilingual audience, this translation loses its principal raison d’être, that is to make the text understandable for foreign readers, but it fulfils other functions.